Strictly or Semitrivial Principal Eigensurface for (p,q)-Biharmonic Systems - DOUMATE, TELE JONAS; LEADI, LIAMIDI ARÈMOU; Toyou, Robert L. (My University, 2022)
This paper extends the eigensurface of p-bilaplacian operator to examine existence and simplicity of the first eigensurface for the third-order spectrum of (p,q)-biharmonic systems subject to boundary conditions.
Keywords: Nonlinear eigenvalue problem; p-biharmonic operator; eigensurface